Domain wall-grain boundary interactions in polycrystalline Pb(Zr0.7Ti0.3)O3 piezoceramics. Issue 12 (September 2020) - Schultheiß, J.; Checchia, S.; Uršič, H.; Frömling, T.; Daniels, J.E.; Malič, B.; Rojac, T.; Koruza, J.
Abstract: Interactions between grain boundaries and domain walls were extensively studied in ferroelectric films and bicrystals. This knowledge, however, has not been transferred to polycrystalline ceramics, in which the grain size represents a powerful tool to tailor the electromechanical and dielectric response. Here, we relate changes in dielectric and electromechanical properties of a bulk polycrystalline Pb(Zr0.7 Ti0.3 )O3 to domain wall interactions with grain boundaries. Samples with grain sizes in the range of 3.9–10.4 μm were prepared and their microstructure, crystal structure, and dielectric/electromechanical properties were investigated. A decreasing grain size was accompanied by a reduction in large-signal electromechanical properties and an increase in small-signal relative permittivity. High-energy diffraction analysis revealed increasing microstrains upon decreasing the grain size, while piezoresponse force microscopy indicated an increased local coercive voltage near grain boundaries. The changes in properties were thus related to strained material volume close to the grain boundaries exhibiting reduced domain wall dynamics.